“The School for the Travellers and the Blacks”: Student and Teacher Perspectives on “Choosing” a Post-Primary School with a High Concentration of Disadvantage - Hannagh Mc Ginley; Elaine Keane (Education Sciences, 2021)
Since the formation of the Irish State, the participation and attainment in education of members of the Irish Traveller community have been low. In terms of school-related factors, research points to Travellers perceiving the curriculum as irrelevant, experiencing problematic relationships with peers and teachers, a strong sense of not belonging, and low teacher expectations. This paper draws on the findings of a wider study which explored how an intercultural approach to education was conceptualised and enacted, with particular reference to Travellers, in one urban DEIS (disadvantaged) post-primary school in the West of Ireland (St. Greg’s) with a highly diverse student population. Located in the interpretivist/constructivist paradigm, and informed by critical race theory, an in-depth qualitative case study research design was employed. Data collection involved twenty-eight semi-structured interviews with teacher and student participants, including Traveller and “other” minority ethnic students, as well as White settled Irish students. Data analysis involved several coding stages, and the development of categories. In this paper, we examine one of the categories, the participants’ perceptions of the school as being a school “for the Travellers and the Blacks” and its “reputation” in this regard, as well as the factors impacting the “choice” of the school by different groups of students. Both teacher and student participants were aware of the school’s negative reputation and how this was associated with the socio-demographic composition of its student population. Regarded as the school “for the Travellers and the Blacks”, it was seen as a “tough” school and one in which academic expectations were low. Choosing St. Greg’s was perceived as being related to having a family history of attending the school, not being able to access other schools, and the school providing supports and “freebies”. The findings are discussed in the context of previous research, focusing in particular on critical issues of school socio-demographics, reputation, and choice. The paper concludes with observations about the problematic nature of Ireland’s increasingly segregated schooling system and recommendations about how the education system might better work to include and support Traveller and other minority ethnic students in post-primary education.